El fenómeno de la informalidad y su contribución al crecimiento económico: el caso de la ciudad de Guayaquil - Véliz Torresano, José (2014)
Under-employment or informality is a compelling truth in developing countries, and Ecuador is no exception, least of all the city Guayaquil. This descriptive study attempts to investigate informality, its reality and characteristics, and especially the contribution to economic growth and its potential in future urban development, by determining the variables that influence the non-formalization of its activities. The results support that informality may be seen as an enterprise mechanism or associated phenomenon. The activities carried out by individuals in an informal way have an impact, not to the extent expected, on the production and growth of a city or region.